Domestication and the Preservation of Wildness: The Self and the Other in Primitive Art Collecting - Derlon, Brigitte; Jeudy-Ballini, Monique (Material Culture Review, 2014)
Abstract Based on the findings of an ethnographic study conducted in France, this paper examines the fundamental ambivalence of the perception of and relation to objects among primitive art collectors. As we guess, the fascination for primitive artifacts is closely related to the taste for the exotic. But our study shows that the integration of primitive artifacts in the private space of an art collection invariably involves a process of domestication that enables collectors to recognize themselves in the domesticated object. In short, the findings suggest that the practices and representations of collectors are marked by a tension between a fascination for otherness and a quest for closeness and familiarity.